Exploratory axis factoring for identifying the self-esteem latent factors and their correlation with the life quality of persons suffering from vitiligo - Fekete, Laszlo; Iantovics, Laszlo Barna; Fekete, Gyula Laszlo (Frontiers in Psychology, 2023)
Objective: Our research aimed to measure the importance of self-esteem in assessing disease burden in patients with vitiligo, which, according to our knowledge, had not been studied before. The research was realized to extend the stage of knowledge regarding the influence of vitiligo on patients' life quality focused on self-esteem. We have formulated the following two hypotheses: H1: two latent factors characterize the self-esteem of patients with vitiligo; H2: the self-esteem of the patients with Vitiligo is correlated with their life quality, by influencing it to a high degree. Results For Q1 it was obtained Cα=0.84. H1 has been proved, as a result of PAF applied on Q1, with the extraction of two latent factors of self-esteem that we named Competence (eigenvalue=4.126; %41.258 of total variance explained) and Value (eigenvalue=1.857; %18.57 of total variance explained). For the two subscales determined by the two factors, we have obtained the Cα by 0.848 and 0.8, all indicating good reliability. For testing H2, on Q2 data we obtained Cα= 0.914. The Spearman correlation coefficient r=-0.734 (p<0.0001), between the self-esteem questionnaire evaluation result and the life-quality index result indicated the existence of a strong negative correlation, which is significant according to 95% CI [-0.81, -0.63]. Discussion In this manuscript, it was studied the self-esteem of patients with vitiligo. Also, there were analyzed the psychometric properties of the Q1 questionnaire. Q1 proved to have good internal consistency. PAF indicated a two-factorial structure, with factors called Competence and Value, proving H1, with a moderate correlation of 0.427 between the two latent constructs. The Competence factor includes motivation, self-efficacy, initiative, and persistence in action. The Value factor is much more complex, indicating a feeling, a personal evaluation, or a positive or negative attitude towards one's person, which better captures the entire phenomenology of self-esteem. The statistical analysis of the results provided by the self-esteem questionnaire included questions that proved to be internally consistent. The AVE and CDV assumptions were met. Q2 was proved to have excellent scale reliability. H2 proved a statistically significant strong negative correlation between the Rosenberg score and DLQI score.